RELEVANSI HUKUM PROGRESIF TERHADAP HUKUM ISLAM - Muhammad Samsuri (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
One of the most interesting legal ideas in the current legal literature of Indonesia is progressive law. This is because progressive law has challenged the existence of modern law which has so far been considered established in punishment. The law reveals the veil and overthrows the failures of modern law based on positiveistic, legalistic and linear philosophy to address issues developed in accordance with the law as a matter of human and humanity. Progressive law contains the liberating spirit of liberation from the legalistic and linear conventional legal conviction. Running a law is not merely textual legislation but in running the law must be by determination, empathy, dedication, commitment to the suffering of the nation to dare to find another way to prosper human. Progressive law starts from a basic assumption, law is an institution that aims to bring people to a life of justice, prosperity and make people happy. The flexibility of the development of Islamic legal thought is highly relevant to introducing the ethos of progresivism in the dynamics and crystallization of Islamic law. The implication of this progressive mode of thinking is the liberation of mankind from mythological, passive and aggressive-conservative things. On the basis of this progressive ethos, it is recognized the capacity of the free will, free act.